Are sandstone miners abused in India? - Ahmad, Absar (Indian Journal of Community Health, 2015)
Despite engaged in economic activities, the situation of sandstone miners is very poor in India. They are abused in many ways like in socioeconomic status, in Physical health, by doctors, by thekedars (contractor), by dacoits and by the administration. This report is compiled on the basis of author Ph.D. field work scheduled in May to September 2014 in 10 sampled villages in Karauli, Rajasthan and collected information from more than 300 mine workers and two in-depth interviews from local newspaper journalists. Karauli is a district of Rajasthan in western India, located at 26.5°N 77.02°E and encompasses an area of 5530 sq km. Located at a distance of 190 km from pink city Jaipur; the maximum temperature here reaches 470C in summers and minimum drops to about 40C in winters! The area is mainly famous for pink colored construction stone used for carving and other decorative materials. The livelihood of the rural population of this district is mainly agriculture, animal husbandry, and mining; with about one-third population dependent on mining for their livelihood. The sandstone famously called Karauli stone is mined here, mostly as an unorganized way. Despite engaged in economic activities and mentioned in the census under Industrial category (Mining and quarrying), the situation of these miners is very poor. They are abused in many ways like in socioeconomic status, in Physical health, by doctors, by thekedars (contractor), by dacoits and by the administration.